Domestic scrutiny of European Union politics: Between whistle blowing and opposition control - Finke, Daniel; Dannwolf, Tanja (European journal of political research, 2013)
Some European law proposals are subject to scrutiny by national parliaments while others go unchecked. The analysis in this article indicates that the opposition scrutinises European Union law to gather information on the proceedings inside the Council of Ministers and the European Parliament. Yet whereas strong opposition parties scrutinise highly politicised law proposals, weak opposition parties tend to scrutinise those proposals that are negotiated under the non-transparent fast-track procedure. In addition, there is ample evidence that the leading minister initiates scrutiny in order to strengthen his or her intergovernmental bargaining leverage. Yet, this Schelling Conjecture presumes that the party of the minister is located between the expected bargaining position in the Council and the coalition partner. Any other domestic interest constellation could lead to scrutiny motivated by whistle blowing. However, an issue's salience helps us to separate the whistle blowing from the Schelling Conjecture.
Gesehen am 06.04.2021